Curcumin and Andrographis Exhibit Anti-Tumor Effects in Colorectal Cancer via Activation of Ferroptosis and Dual Suppression of Glutathione Peroxidase-4 and Ferroptosis Suppressor Protein-1 - Katsuki Miyazaki; Caiming Xu; Mitsuo Shimada; Ajay Goel (MDPI AG, 2023)
Colorectal cancer (CRC) is the leading cause of cancer-related deaths worldwide. The limitations of current chemotherapeutic drugs in CRC include their toxicity, side effects, and exorbitant costs. To assess these unmet needs in CRC treatment, several naturally occurring compounds, including curcumin and andrographis, have gained increasing attention due to their multi-targeted functionality and safety vs. conventional drugs. In the current study, we revealed that a combination of curcumin and andrographis exhibited superior anti-tumor effects by inhibiting cell proliferation, invasion, colony formation, and inducing apoptosis. Genome-wide transcriptomic expression profiling analysis revealed that curcumin and andrographis activated the ferroptosis pathway. Moreover, we confirmed the gene and protein expression of glutathione peroxidase 4 (GPX-4) and ferroptosis suppressor protein 1 (FSP-1), the two major negative regulators of ferroptosis, were downregulated by this combined treatment. With this regimen, we also observed that intracellular accumulation of reactive oxygen species and lipid peroxides were induced in CRC cells. These cell line findings were validated in patient-derived organoids. In conclusion, our study revealed that combined treatment with curcumin and andrographis exhibited anti-tumorigenic effects in CRC cells through activation of ferroptosis and by dual suppression of GPX-4 and FSP-1, which have significant potential implications for the adjunctive treatment of CRC patients.